Inherent Third-Harmonic Circulating Current in Delta-CHB STATCOM: Analysis and Compensation - Joao Victor Guimaraes Franca; Dayane Do Carmo Mendonca; Heverton Augusto Pereira; Yu Jin; Qian Xiao; Allan Fagner Cupertino (IEEE Access, 2025)
The Delta-connected Cascaded H-Bridge (Delta-CHB) is one of the most commonly adopted topologies for Static Synchronous Compensator (STATCOM) systems. Due to the oscillating instantaneous power resulting from the multiplication of sinusoidal voltage and current, a second-order harmonic arises in the Delta-CHB dc-link. In addition to increasing the required capacitance, it introduces a third-harmonic circulating current (THCC), increasing power losses and semiconductor stress. This paper analytically describes this phenomenon and compares two suppression strategies. The proposed model stands out for its simplicity and effectiveness in STATCOM applications, providing a straightforward approach to estimating both the circulating current and the capacitor voltage ripple, also accounting for their mutual influence. The capacitor voltage model exhibited errors lower than 4.5% compared to the simulation and lower than 6.9% compared to the experiment. Similarly, the circulating current model showed an error lower than 3.1% compared to the simulation and under 15% in the experiment. The first suppression strategy analyzed, which involves adding a resonant controller for the circulating current, was able to practically eliminate the circulating current. The second suppression strategy, based on normalization, reduced the circulating current by 30.27% in the experiment, demonstrating sensitivity to the measurement and control implementation delays.